2013
DOI: 10.1021/ac400989p
|View full text |Cite
|
Sign up to set email alerts
|

Paper Analytical Devices for Fast Field Screening of Beta Lactam Antibiotics and Antituberculosis Pharmaceuticals

Abstract: Reports of low quality pharmaceuticals have been on the rise in the last decade with the greatest prevalence of substandard medicines in developing countries, where lapses in manufacturing quality control or breaches in the supply chain allow substandard medicines to reach the marketplace. Here, we describe inexpensive test cards for fast field screening of pharmaceutical dosage forms containing beta lactam antibiotics or combinations of the four first-line antituberculosis (TB) drugs. The devices detect the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 34 publications
1
84
0
2
Order By: Relevance
“…Substandard drugs can be detected by different methods, including inspection, colorimetric methods, chromatography, and spectrometry (Table 3) (9,12,31,43,45,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106). A three-level approach (107) consisting of different quality control procedures has been proposed to detect substandard/counterfeit antimicrobials.…”
Section: Methods Used To Detect Counterfeit/substandard Antimicrobialsmentioning
confidence: 99%
“…Substandard drugs can be detected by different methods, including inspection, colorimetric methods, chromatography, and spectrometry (Table 3) (9,12,31,43,45,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106). A three-level approach (107) consisting of different quality control procedures has been proposed to detect substandard/counterfeit antimicrobials.…”
Section: Methods Used To Detect Counterfeit/substandard Antimicrobialsmentioning
confidence: 99%
“…Acetaminophen, the active ingredient in Tylenol, has been reported as a commonly incorporated cheaper substitute present in counterfeits because of its ability to reduce fever and pain, leading the patient to believe that the medicine is producing a therapeutic effect [13]. Acetaminophen and other common, relatively inexpensive inactive ingredients were used to make the simulated counterfeits in this study.…”
Section: Resultsmentioning
confidence: 99%
“…One approach to perform equipment-free analysis relies upon color intensity comparators using an external calibration or standard calibration integrated within the device [143,144]. Weaver et al reported a cost-effective "color barcode" test for the rapid screening and quality control of pharmaceutical drugs [145]. The fabricated device was divided into twelve individual lanes, on which the solid pharmaceutical product was mounted and the edge dipped into the chosen media.…”
Section: Readout Outcomesmentioning
confidence: 99%
“…Each lane specifically reacted to one type of analyte (e.g., ampicillin, amoxicillin, and rifampicin) and a corresponding colored lane, visually compared with the reference was indicative of a "positive I.D." [145]. Another interesting study by Zhu et al reported a self-calibrating sensor for glucose measurement.…”
Section: Readout Outcomesmentioning
confidence: 99%